ZIARE ŞI REVISTE FONDATE PESTE HOTARE DE CETĂŢENII MOLDOVENI EMIGRAŢI: PARTICULARITĂŢI ŞI EVOLUŢIE - Deleu, Ecaterina (CEP USM, 2020)
The newspapers and magazines published abroad, founded by emigrated Moldovan citizens, bring added value to the national press as a source of information and documentation on the realities of the host countries, as well as on the situation of emigrated persons. This media phenomenon represents another aspect of the socio-cultural process that is currently happening abroad, with different characteristics at different stages in the process of integration of Moldovan emigrated citizens. The purpose of our research is to analyze the stages of the evolution of magazines published abroad by emigrated Moldovan citizens, their role in the context of the development of the Romanian language press abroad, their specificity and typology, the ways of reflecting the situation of migrants, in an attempt to become a bridge between the communities formed in the host country and the country of origin, a gateway to the community of emigrated citizens.
Keywords: media; newspapers; magazines; diaspora; moldovan migrants